Single-cell analysis of autophagy activity in normal and de novo transformed human mammary cells - Lefort, Sylvain (Sci Rep, 2020)
Assessment of autophagy activity has historically been limited to investigations of fixed tissue or bulk cell populations. To address questions of heterogeneity and relate measurements to functional properties of viable cells isolated from primary tissue, we created a lentiviral (RFP-GFP-MAP1LC3B) vector that allows the autophagosome and autolysosome content of transduced cells to be monitored at the single-cell level. Use of this strategy to analyze purified subsets of normal human mammary cells showed that both the luminal progenitor-containing (LP) subset and the basal cells (BCs) display highly variable but overall similar autophagic flux activity despite differences suggested by measurements of the proteins responsible (i.e., LC3B, ATG7 and BECLIN1) in bulk lysates. Autophagosome content was also highly variable in the clonogenic cells within both the LPs and BCs, but the proliferative response of the BCs was more sensitive to autophagy inhibition. In addition, use of this vector showed cells with the lowest autophagosome content elicited the fastest tumor growth in 2 different models of human mammary tumorigenesis. These results illustrate the utility of this vector to define differences in the autophagy properties of individual cells in primary tissue and couple these with their responses to proliferative and oncogenic stimuli.